COMPARATIVE ANALYSIS OF CONTEMPORARY SLAVERY IN WEST AFRICA - Gyuracz, Veronika (European Scientific Journal, ESJ, 2014)
This article aims to provide a study of slavery from a comparative point of view. Precisely, it looks for the root causes of the similar coverage and structure of traditional and contemporary slavery in West Africa. After determining the necessity of using the term of contemporary slavery for nowadays’ human rights violations, the article provides the comparison of traditional and modern day slavery in Mauritania and Ivory Coast where chattel slavery and child labor still keep a lot of people in bondage. The author states that infractions were basic components of the traditional slave trade in the early modern and modern age, while they are still determining factors of these two countries’ society and economy. Following the two case studies, the author discusses the efforts of the international community to abolish slavery by analyzing related legal instruments and it also looks into the mandate of the Special Rapporteur on all Forms of Contemporary Slavery. This part confirms the need for an increasing attention of the governmental and non-governmental actors of international politics to the issue of slavery.